Construcción de un módulo de sobrecorriente para simular el comportamiento de los relés 50 y 51 en régimen permanente de una falla eléctrica - Panchi Guamangallo, Alex Danilo (2018)
As far as it is concerned, in power electric systems (SEP), it is quite important to guarantee the electric service continuity before being witness of power failure as well as safeguarding the good condition of equipment which is part of SEP. To achieve this goal, a lot of different equipment such as timed and instant overcurrent relay is used. This project was focused on the construction of an overcurrent relay prototype of instant and inverse time based on mathematical models stated on IEC 2554 and BS142 norms. The module embraces a human-machine interphase (HMI) that makes it easier to read the dialling of variables for its calibration. The current signal is measured through an effect hall sensor that is connected to an analogic input from Arduino card. The signal is processed so that an efficient value is obtained and as a result measured value is represented in a current transformer (CT). The prototype calculates the operating time at different Dial and Tap, the module has a minimum response of 9 milliseconds that is enough set time to process current RMS value. The contact opening-up from instant time is at millisecond range. Didactic relays will be put together to operate the equipment of electric machines that are in the laboratory of the Technical University of Cotopaxi. Through the use of the didactic module, students will be able to conduct coordination testing of protection and verification of operating times at different failures in permanent patterns. Thus, this module proves to be easy and friendly with the actual users.